An integrated effort of medium reactivity fuel, in-cylinder, and after-treatment strategies to demonstrate potential reduction in challenging emissions of reactivity controlled compression ignition combustion. (April 2020) - Murugan, R; Ganesh, D; Nagarajan, G
Previous studies on reactivity controlled compression ignition combustion indicated that, reducing the hydrocarbon and carbon monoxide emissions at low load conditions still remains a challenge because of lower in-cylinder temperatures due to lower global reactivity gradient and reduced oxidation process. Research in this direction has not been reported so far and with this motivation, an attempt has been made to increase the global reactivity gradient and oxidation of fuel–air mixture by converting the low reactivity fuel methanol into medium reactivity fuel. This is achieved by mixing high octane oxygenated fuel, methanol (Octane Number: 110), with an oxygenated better cetane and volatility fuels like polyoxymethylene dimethyl ether (Cetane Number: 78) and isobutanol (Cetane Number: 15). The medium reactivity fuel with multiple direct injection of diesel fuel timed the combustion of dual fuel–air mixture to avoid too late or too advanced combustion which are the prime factors in controlling the unburnt emissions in a low temperature combustion process. Four medium reactivity fuel samples, M80IB20, M60IB40, M90P10, and M80P20, on percentage volume basis have been prepared and tested on the modified on-road three-cylinder turbocharged common rail direct injection diesel engine to demonstrate higher indicated thermal efficiency and potential reduction in unburnt and oxides of nitrogen/particulate matter emissions from reactivity controlled compression ignition combustion. Experimental results show that, use of medium reactivity fuel with optimized diesel injection strategy resulted in 66% decrease in hydrocarbon emission and 74% decrease in carbon monoxide emission by enhancing the oxidation of fuel–air mixture at lower temperatures which is evidently noticed in the combustion characteristics. Further reduction in hydrocarbon and carbon monoxide emission of about 90% has been achieved by integrating the diesel oxidation catalyst with the engine.